2018
DOI: 10.3390/genes9080408
|View full text |Cite
|
Sign up to set email alerts
|

Authenticity Testing and Detection of Eurycoma longifolia in Commercial Herbal Products Using Bar-High Resolution Melting Analysis

Abstract: The present study demonstrated High Resolution Melting (HRM) analysis combined with DNA barcode (Bar-HRM) as a fast and highly sensitive technique for detecting adulterants in Eurycoma longifolia commercial herbal products. Targeting the DNA barcoding of the chloroplastic region-ribulose biphosphate carboxylase large chain (rbcL) and the nuclear ribosomal region- internal transcribed spacer 2 (ITS2), PCR amplification and HRM analysis using saturated Eva green dye as the source of fluorescence signals, was acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The advantage of HRM is its capacity to screen variations in speci c regions that would not be identi ed by Sanger sequencing; moreover, using HRM analysis of melting temperatures can allow any different nucleotides in a sequence to be detected 31 . Recent studies have shown that Bar-HRM analysis can be effective in providing consistent shapes and pro les of melting curves that correspond to very closely related medicinal plant species and allow the authentication of herbal products 19,[23][24][25] . Nucleotide composition and DNA length are affected by the dissociation step of double-stranded amplicons in HRM analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of HRM is its capacity to screen variations in speci c regions that would not be identi ed by Sanger sequencing; moreover, using HRM analysis of melting temperatures can allow any different nucleotides in a sequence to be detected 31 . Recent studies have shown that Bar-HRM analysis can be effective in providing consistent shapes and pro les of melting curves that correspond to very closely related medicinal plant species and allow the authentication of herbal products 19,[23][24][25] . Nucleotide composition and DNA length are affected by the dissociation step of double-stranded amplicons in HRM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the shortcomings of the PCR-RFLP approach are that it is time consuming and very limited in its ability to identify species when the samples are from incomplete specimens or damaged. More recently, several studies have shown that very closely related medicinal plant species can also be distinguished accurately by using DNA barcoding combined with highresolution melting (Bar-HRM) analysis 19,[23][24][25] .…”
mentioning
confidence: 99%
“…ITS2F 5¢-ATGCGATACTTGGTGTG AAT-3¢ ITS3R 5¢-GACGCTTCTCCAGACTACAAT-3¢ rbcLa-F: 5¢-ATGTCACCACAAACAGAGACTAAAGC-3¢, rbcLa-R: 5¢-GTAAAATCAAGTCCACCRCG-3¢. 14,30 For rbcL, the amplification conditions were as follows: an initial denaturation at 95°C followed of 30 cycles of 55°C for 1 min, and 72°C for 1 min. 32 The fluorescent data were acquired at the end of each extension step during PCR cycles.…”
Section: Real-time Pcr and Hrm Analysismentioning
confidence: 99%
“…25,26 In addition, the chloroplast ribulose bisphosphate carboxylase large chain gene (rbcL) is another barcode region used in most land plants due to the ease of amplification, the availability of databases 21,[27][28][29] and its potential application for authenticity testing. 30 Several other cannabis chloroplast markers have been used for forensic purposes (e.g., to establish the geographical origin of seizures). 18 Therefore, we proposed a method based on the ITS2 nuclear DNA region and rbcL, a chloroplast marker, combined with HRM-PCR, for detection of adulterants in cannabis seeds commercial strains.…”
Section: Introductionmentioning
confidence: 99%
“…Due to high demand of this plant there are various formula of E. longifolia are available in health food market, in crude drug powder form or capsules which contain crude drug powder or E. longifolia extract (Effendy et al, 2012). It can be found as health supplements in capsules, tablets and beverages (Fadzil et al, 2018). Nowadays, root extract of E. longifolia used as pre-mixed in tea, coffee and carbonated drink which sales in commercial market (Low et al, 2013).…”
Section: Traditional Usesmentioning
confidence: 99%